Konsumsi tinggi lauk hewani, rendah sayur dan rendah aktivitas fisik berhubungan dengan kejadian kelebihan berat badan pada anak sekolah dasar - Triandhini, R.L.N.K. Retno; Kinasih, Angkit; Sriwijayanti, Anik (Department of Nutrition Science, Faculty of Medicine, Universitas Diponegoro, 2018)
Background : Overweight and obesity in children are becoming a global health issue that needs special attention. Overweight currently occur not only in urban areas but also in rural areas. One factor that affects over nutrition is the imbalance between food intake and physical activity. Objective : The objective of this study is to analysis differences in food pattern and physical activitiy between overweight and normal children. Methods : This study was used cross sectional design. Samples were 10-12 year olds students from 13 elementary schools in Getasan Subdistrict. Dietary intake were measured by Food Frequency Questionnaire (FFQ) form and physical activity were measured by Physical Activity Questionnaire For Older Children (PAQ-C) form. Data were analyzed by Chi-Square and independent t test. Results : There are significant correlation between physical activity and the incidence of overweight in children (Ï=0,003). There are significant differences (Ï<0,05) in carbohydrates, animal protein, plant protein and vegetables intake (Ï=0,001, Ï=0,001, Ï=0,001, Ï=0,001) between normal and overweight groups.Conclusion : There are significant correlation between physical activity and the incidence of overweight in children. There are significant differences in carbohydrates , animal protein, plant protein and vegetables intake between normal and overweght groups.